HUBUNGAN TINGKAT PENGETAHUAN DENGAN TINDAKAN PENCEGAHAN KANKER SERVIKS PASCA PENYULUHAN PADA WANITA USIA SUBUR - Farida Anwari, Acivrida Mega Charisma (AKADEMI FARMASI JEMBER, 2017)
Cervical cancer is the number one cause of death in Indonesian women. Cervical cancer is a malignant tumor that grows inside the cervix / cervix is the lowest part of the uterus that attaches to the top of the vagina. The high number of cases is due to limited access to screening, treatment and lack of information and services to the disease. This cervical cancer can be detected early by doing pap smaer examination.This study aims to determine the relationship between the knowledge level of cervical cancer and its prevention measures in women of childbearing age in Kabupatn Gresik East Java.Design The research used is descriptive, data collection using questionnaires given to women participants counseling in Gresik district of East Java with the total population of 68 respondents and the number of samples were 53 respondents, the selection of respondents based on age is fertile age (15-46 years), married and sexually active.The result of this research by using chi square test showed that there was no significant correlation between age with cervical cancer prevention at post counseling (ρ = 0.187 α = 0.05), there was a significant correlation between level of knowledge with precancement of cervical cancer at post counseling (ρ = 0.025 α = 0.05).It is hoped that this research can be a reference for health workers in counseling about cervical cancer in women of childbearing age throughout Indonesia, and suggest that people can increase their knowledge about servical cancer and can take precautions by avoiding the risk factors of cervical cancer.Keywords : Knowledge of cervical cancer, cervical cancer risk factor, Prevention of cervical cancer